Streamlining Disaster and Incident Reporting using MyAssist - Fadilah Daud; Norfaradilla Wahid (Applied Information Technology And Computer Science, 2023)
Abstract: Technological approaches were made to prevent and prepare in any case of emergency. The main objective of the project is to design and develop a mobile application for improving disaster preparedness where it emphasizes location monitoring, hazard alert, and sending complaints related to disasters. Furthermore, this project analyses other literary works by comparing existing applications and conducting a survey to analyse the requirements from different sources. Information gathered from the surveys is used to construct the nature of the applications by forming structured diagrams and designing wireframes for interfaces. The project development followed the Agile principle while implementing the modules and functions in Java language using Android Studio IDE. By the end of this project, the outcomes of the application are tested to show the reliability of the application where the result of the test shows the application meets the user satisfaction.